2022
DOI: 10.31138/mjr.33.4.430
|View full text |Cite
|
Sign up to set email alerts
|

The Anxiety and Depression in Rheumatoid Arthritis Patients Treating with Disease-Modifying Anti-Rheumatic Drugs during the COVID-19 Pandemic

Abstract: Objective: Anxiety and depression are associated with the risk of illness, presence of physical symptoms, and poor health in the COVID-19 epidemic. Our aim is to assess the severity of anxiety and depression in rheumatoid arthritis (RA) patients treated with disease-modifying anti-rheumatic drugs during the COVID-19 pandemic. Material and methods: The study is a longitudinal, hospital-based survey study including 102 RA patients receiving disease-modifying anti-rheumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, impaired coping responses to pain, fatigue, and disability in patients with depression reduce physical exercise and social interaction, leading to poorer RA outcomes [ 16 ]. Although some studies found that features like marital status, gender, and socioeconomic level can cause mood disorders in RA, other reports failed to establish such associations [ 17 , 18 , 19 ]. On the other hand, factors for optimal sleep for those with RA are a lower body mass index, better quality of life, treatment, and disease remission [ 14 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, impaired coping responses to pain, fatigue, and disability in patients with depression reduce physical exercise and social interaction, leading to poorer RA outcomes [ 16 ]. Although some studies found that features like marital status, gender, and socioeconomic level can cause mood disorders in RA, other reports failed to establish such associations [ 17 , 18 , 19 ]. On the other hand, factors for optimal sleep for those with RA are a lower body mass index, better quality of life, treatment, and disease remission [ 14 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%